Aromatization of ethylene over zeolite-based catalysts. Issue 9 (16th January 2020) - Uslamin, Evgeny A.; Saito, Hikaru; Kosinov, Nikolay; Pidko, Evgeny; Sekine, Yasushi; Hensen, Emiel J. M.
Abstract : Elucidating the role of metal modification and confined hydrocarbon species in the aromatization of ethylene on zeolite catalysts. Abstract : Light aromatic compounds (BTX: benzene, toluene and xylenes) represent an important class of building blocks in the chemical industry. Currently, light aromatics are obtained exclusively from fossil feedstock, whose utilization is associated with serious environmental concerns. Developing new routes for a more sustainable BTX production is, therefore, of high importance. In this work, aromatization of ethylene over well-defined metal-modified HZSM-5 zeolite catalysts is examined. The results show that modification of zeolite with gallium, zinc and silver leads to a significant increase in aromatics production. Metal species are responsible for catalysing dehydrogenation pathways with Ga being the most efficient for BTX production. Increasing temperature and ethylene partial pressure facilitate ethylene aromatization. Employing a combination of isotope labelling with a thorough characterization of zeolite-entrapped species by means of IR and MAS NMR spectroscopy provides evidence for the involvement of intra-zeolite aromatic hydrocarbon species in the catalytic cycle.